Sistem Informasi Pelayanan dan Pengelolaan Rukun Tetangga (SIPP RT) Menggunakan Metode Depth First Search Berbasis Web - Nababan, Andre Fernanta; Natashia, Novi Dian (Forum Kerjasama Pendidikan Tinggi, 2022)
The government system in Indonesia is divided into several levels, starting from the central government, regional government, to the smallest at the RT (neighborhood) level. At the RT level, administrative services and management, such as citizen data collection, financial reporting, providing information, and so on, are still mostly done manually so that their service practices are not optimal. Therefore, we need a system that can improve services at the RT level. With the design of a service information system and neighborhood management using the web-based DFS (depth first search) method, it is hoped that it can improve the services of RT management and make it easier for residents to search for information at the RT level. This system is made using the PHP programming language and MySQL as the database. The method used is DFS (depth first search) because it can optimize the web in searching for information based on the keywords entered so as to shorten the time in getting the information needed in RT services and management